Perbaikan Kualitas Layanan Pesantren Berbasis Kebutuhan Santri: Implementasi ServQual dan QFD - Rahim, Abdul; Supriadi, Yudi Nur; Iswanto, A Heri (PAKAR Pendidikan, 2025)
The quality of education is a crucial factor for the progress of the nation in forming a high-capacity and moral society. Pesantren, as boarding educational institutions in Indonesia, have more complex service demands than non-Islamic boarding schools because they manage formal and non-formal programs. Initial studies at Islamic Boarding School XYZ showed that there had been no improvement in services based on Voice of Customer. This study aims to maximize the quality of Islamic Boarding School XYZ services by focusing on the five dimensions of SERVQUAL (physical evidence, reliability, responsiveness, assurance, and empathy). Data collection was carried out through questionnaires distributed to students as respondents. Data analysis was carried out by implementing the SERVQUAL method to identify service gaps and Quality Function Deployment (QFD) to formulate action plans based on improvement priorities. The results of the study identified 19 service attributes that needed improvement. These improvement recommendations were compiled based on a comprehensive analysis using SERVQUAL and QFD, providing concrete guidance for XYZ Islamic Boarding School to effectively improve the quality of services based on the needs of students.